The Thermal Effect of Variate Cross-Sectional Profile on Conformal Cooling Channels in Plastic Injection Moulding - Wahab, Md Saidin; Ahmad Raus, Azli; Amir, Irwan; Ahmed, Aqeel; Kamarudin, Khairu (International Journal of Integrated Engineering, 2018)
Cooling system is an important role in designing a productive plastic injection moulding (PIM). The selection of geometry and layout for plastic injection moulding cooling channels strongly influences the cooling performance such as cooling time and thermal distribution that leads to shrinkage and warpage. This paper presents the study to determine the best cooling channel layout and cross-sectional profile which include circular straight drilled cooling channels, circular conformal cooling channels, square shape conformal cooling channels, elliptical conformal cooling channels and diamond conformal cooling channels. The cooling time and thermal distribution were simulated by Moldflow Insight (MFI) software. Results are presented based on ejection time and temperature variation by using transient analysis in MFI. The results found the best cross-sectional of cooling channels indicated by square shape conformal cooling channels, compare to others due to the shortest cooling time that recorded from simulation. The conformal cooling channel layout also resulted greater thermal distribution compared to straight drilled cooling channel design.Â Â